Islamic Perspective of the Learning Organization - Aini, Ahmad (Edward Elgar Publishing, 2013)
The adaptation of learning organizations in different contexts has become a well-discussed topic. However, not much has been written on learning organizations in a religious context. One of the very few examples that can be found is a study of spiritual themes in the characteristics of learning organization by Porth et al. (1999). They suggest that: ‘the learning organization’s emphasis on the primacy of human intellect that produces ongoing innovation has many affinities with social teachings from the Christian and Judaic traditions’ (Porth et al. 1999, p. 217) Therefore, a study of the Islamic perspective on the learning organization concept is relevant and timely. There is clear evidence of the learning element and the importance of learning in Islamic organization. My previous work that deals with the Islamic perspective on the learning organization is Ahmad (2010). This chapter discusses whether the idea of the learning organization is applicable in the Islamic environment, and is in harmony with the Muslim culture.